Validation of e-psychological instrument for flood victims version-II - Ali, Nazilah; Ibrahim, Raja Zirwatul Aida; Dagang, Mazidah; Rohaizad, Nor Aizal Akmal; Che Wan Ibrahim, Che Wan Ida Rahimah; Abdullah, Norillah (Institute of Advanced Science Extension (IASE), 2019)
This study aims to validate a newly developed of e-Psychological Instrument for Flood Victims Version II (e-PIFV-II) by using expert judgment method. Measuring the psychopathology symptoms among flood victims is an important step for intervention and treatment. However, there is a gap of a valid, reliable and efficient instrument to measure flood victims' mental health in Malaysia. The e-PIFV-II is a digital self-report inventory that has 56 items with 4 dimension scales namely stress, anxiety, depression, and trauma. Results showed that there was strong content coefficient validity for each subscale of the instrument and the coefficient value for trauma subscale in the e-PIFV-II was increased. The coefficient value of stress was 0.8, anxiety was 0.9, depression was 1.0, trauma was 0.9 and overall was 0.9. This study supports the theoretical framework and provides practical implication in the field of clinical psychology and flood management.